A net‐zero Swiss energy system by 2050: Technological and policy options for the transition of the transportation sector. Issue 3 (27th March 2022) - Kannan, Ramachandran; Panos, Evangelos; Hirschberg, Stefan; Kober, Tom
Abstract: The Swiss government sets out a net‐zero emission goal by 2050 while phasing out nuclear energy. This study presents insights on the transport sector's contribution to meet this goal, in terms of which type of vehicle drivetrains and fuel supply options are cost‐effective? What could be critical for the transition of the transportation sector? We use the Swiss TIMES Energy system Model and assess prospective technological scenarios for the whole energy system. The transport module has fast‐charging stations and mechanisms to control e‐mobility charging. Results indicate that extensive direct and indirect electrification of mobility increases the electricity demand up to 22 TWh. While to a certain extent electric cars are competitive even if the climate would not be the priority, carbon neutrality requires a boost for electrified mobility where battery‐ and plug‐in hybrid electric vehicles are largely evolving as a solution for small‐medium size car segments while fuel cell cars are an attractive option for big size car segments. Hybridization of buses and trucks emerges as a competitive option but they are propelled with bio‐ and synthetic fuels. The transport sector emerges as a major driver for the deployment of hydrogen in the energy sector in the long term.